TOURISM POTENTIAL OF THE CITIES OF EXTREME NORTH - Zhigunova, Galina Vladimirovna (Sovremennye issledovaniya sotsialnykh problem, 2015)
This article is devoted to urban tourism development on the territories of Russia’s Extreme North. Scientific novelty of the paper is conditioned by the problem statement, its ground and the conclusions drawn, which are related to the tourism development regulation on the Extreme North of the country.The author shows inequality of demand for tourism services in different parts of the country and reveals the reasons for current difficulties and peculiarities of tourism development on the Extreme North; the author comes to the conclusion that it is necessary to have targeted strategy of urban development in accordance with tourism sphere as a key element of the stra-tegy of the Northern cities development.Methodological and theoretical base of the paper were theoretical statements of urban sociology, theoretical and empirical methods: comparative analysis, synthesis; questionnaire survey.The article results can be used in forming regional tourism development concept in the ci-ties of Extreme North and also in giving a course of lectures in «Urban Sociology». Данная статья посвящена проблеме развития городского туризма на территориях Крайнего Севера России. Научная новизна работы обусловлена постановкой проблемы, ее обоснованием и произведенными выводами, связанными с регулированием развития туризма на крайнем севере страны.Автор, показывая неравномерность востребованности туристических услуг в различных частях страны и выявляя причины существующих трудностей и особенностей в развитии туризма на Крайнем Севере, приходит к выводу, что необходима целенаправленная стратегии городского развития в соответствии с туристической сферой как ключевого элемента стратегии развития северных городов.Методологической и теоретической базой работы послужили теоретические положения социологии города, теоретические и эмпирические методы: сравнительный анализ, синтез; анкетный опрос. Результаты статьи могут быть использованы при формировании региональной концепции развития туризма в городах Крайнего Севера, а также при чтении курса «Социология города».